Cytotoxicity of ethanolic extract of fruit shells and seeds of Nyamplung (Calophyllum inophyllum L.) on WiDr colorectal cancer cells - Irfan Jaen Fathani; Isnatin Miladiyah (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2021)
Background: Colorectal cancer is the 3rd most common type of cancer in the world with unsatisfactory therapeutic effectiveness. One of the efforts being made to overcome this problem is by extracting various new chemotherapy agents, including herbal plants. The Nyamplung plant (Calophyllum inophyllum L.) is reported to contain calophyllolide, triterpene, coumarin, saponin, biflavonoids, benzophenones and neoflavanoids which are potential anticancer agents. Objective: This study aims to determine the cytotoxic activity of ethanolic extract of fruit shells and seeds of Nyamplung (Calophyllum inophyllum L.) on WiDr colorectal cancer cells and their selectivity on normal cells (Vero).Methods: The fruit and seeds of Nyamplung were extracted by maceration with 70% ethanol solvent. The cytotoxic test was carried out by the 3-(4,5-dimethylthiazol-2-yl)-2-5-diphenyltetrazolium bromide (MTT) method, with doxorubicin as a positive control. Data analyzed using Microsoft Excel software using linear regression analysis. The IC50 value and selectivity index were used as indicator of toxicity selectivity.Results: The IC50 value of the ethanolic extract of Nyamplung fruit shells on WiDr was 42.47 µg/ml with a selectivity index of 1.50. Meanwhile, the IC50 value of ethanolic extract of Nyamplung seeds was 1,030.41 µg/ml with a selectivity index of 67,982,414.71. Doxorubicin as a positive control obtained IC50 value on WiDr cells of 3.49 µg/ml with a selectivity index of 764.41.Conclusion: The ethanolic extract of Nyamplung seeds was not cytotoxic against WiDr colorectal cancer cells, while the ethanolic extract of Nyamplung fruit sell was moderate cytotoxic with low selectivity index.